Leveraging agriculture for nutrition in South Asia: What do we know, and what have we learned?. (January 2019) - Gillespie, Stuart; Poole, Nigel; van den Bold, Mara; Bhavani, R.V.; Dangour, Alan D.; Shetty, Prakash
Highlights: A synthesis of five years of research on agriculture and nutrition in South Asia. A systems approach is needed to understand agriculture's contribution to nutrition. Political commitment needs to lead to large-scale action and results on the ground. Leadership, capacity, coherence and coordination are key for progress. Contextual evidence from research on impact pathways should continue to guide decisionmaking. Abstract: Despite significant improvements over recent decades, rates of undernutrition remain high in South Asia, with adverse impacts on morbidity and mortality. Overweight/obesity, among children and adults, is now an additional and major public health concern. While agriculture has the potential to improve nutrition through several pathways, this potential is currently not being realised in the region. The Leveraging Agriculture for Nutrition in South Asia (LANSA) research consortium (2012–2018) set out to improve understanding about how agriculture and related food policies and programs in South Asia (specifically in India, Bangladesh, Pakistan and Afghanistan) can be better conceptualised and implemented in order to enhance impacts on nutrition outcomes, especially those of young children and adolescent girls. This paper provides a snapshot of the agriculture-nutrition nexus in the region, outlines the pathways through which agriculture can influence nutrition outcomes, elaborates on the objectives of the LANSA research consortium within this context, and highlights the core findings of the six papers that form the body of this Special Issue. The paper ends with five key lessons that have emerged from this research, during this decade.